A Metaheuristic Procedure for Calculating Optimal Osmotic Dehydration Parameters: A Case Study of Mushrooms - Yeomans, Julian Scott (Transactions on Engineering and Computing Sciences, 2017)
The Firefly Algorithm (FA) metaheuristic is employed to determine the optimal parameter settings in a case study of the osmotic dehydration of mushrooms. In the case, the functional form of the dehydration model is established through a response surface technique and the resulting mathematical programming is formulated as a non-linear goal programming model. For optimization purposes, a computationally efficient, FA-driven method is used and the resulting optimal process parameters are shown to be superior to those from previous approaches.